From commensalism to pathogenesis: the hidden role of the respiratory virome - Wang, Zhihao; Song, Lei; Li, Dan; Jin, Yuanhui (Frontiers in Cellular and Infection Microbiology, 2025)
The respiratory virome, encompassing both eukaryotic viruses and bacteriophages, is an essential but often overlooked component of the airway microbiome. Recent advances in metagenomics have revealed that a diverse viral community exists even in healthy individuals, contributing to immune regulation and microbial balance. However, the field faces several challenges: the baseline composition of the respiratory virome remains incompletely defined, its immunomodulatory functions are not fully understood, and its contributions to respiratory diseases are only beginning to be elucidated. This mini-review summarizes current knowledge of the respiratory virome under physiological conditions, highlights emerging insights into how resident viruses and phages shape host immunity, and discusses alterations observed in asthma, chronic obstructive pulmonary disease, pulmonary fibrosis, and pneumonia. By integrating evidence across these conditions, we emphasize the significance of the virome in both health and disease. A deeper understanding of its dynamics may yield novel diagnostic markers and therapeutic strategies, underscoring the importance of future longitudinal and mechanistic studies in this rapidly evolving field.